Ahmad Tayyeb's Critique of Hasan Hanafi's Concept of Turots Wa Tajdid - Safitri, Eka (Rumah Moderasi Beragama of Cyber Islamic University Syekh Nurjati Cirebon, 2024)
This article aims to reveal Ahmad Tayyeb's criticism to Hasan Hanafi regarding turots wa tajdid. This criticism conveyed by Ahmad Tayyeb has rational and scientific reasons based on his scientific studies. Ahmad Tayyeb is a prominent Muslim scholar as well as the Grand Sheikh at Al Azhar, Cairo, Egypt. The influence of his thought spanned the world and became one of the most influential Muslim figures. Anxiety currently is the rise of new khawarij understanding so that the emergence of various kinds of terrorism movements, radicalism. Ahmad Tayyeb called for the teaching of peace for all human beings, that all of us are brothers and are equally human beings who deserve to be respected for their human rights. The conclusion of this paper states that Ahmad Tayyeb calls for Traditional Islam which adheres to the text of the Koran in solving problems. Muslims must have principles in upholding Islamic law in relation to various fields, not continue to adhere to western principles because Islam also has its own. The spirit of peace between religious communities is something that must be held firmly because Islam is a religion that loves peace